SNAP25-induced MYC upregulation promotes high-grade neuroendocrine lung carcinoma progression - Chen, Zhiqiang; Wang, Shujing; Wang, Jingrui; Wang, Ying; Qi, Xiangjun; An, Bo; Sun, Lingling; Lin, Lizhu (Frontiers in Immunology, 2024)
Background This study investigated the expression and role of Synaptosome associated protein 25 (SNAP25) in high-grade neuroendocrine carcinoma (HGNEC). Methods We used differentially expressed analysis and weighted gene co-expression network analysis (WGCNA) to identify key genes and modules in HGNEC. KEGG and GO analyses helped understand these genes’ roles, and ROC curves assessed their diagnostic value. We also studied SNAP25’s relation to immune infiltration and confirmed findings with in vitro and vivo experiments and datasets. Results WGCNA identified 595 key genes related to pathways like MAPK signaling, GABAergic synapse, and cancer-related transcriptional misregulation. Top genes included SNAP25, MYC, NRXN1, GAD2, and SYT1. SNAP25 was notably associated with M2 macrophage infiltration. Dataset GSE40275 confirmed SNAP25’s high expression and poor prognosis in HGNEC. qRT-PCR and WB analyses showed increased SNAP25 and c-MYC levels in HGNEC, promoting MEK/ERK pathway activity. Reducing SNAP25 decreased H1299 cell proliferation, migration, invasion, and levels of c-MYC, MEK, and ERK. Finally, in vivo experiments further confirmed that SNAP25 knockout can inhibit tumor growth. Conclusion SNAP25 regulates c-MYC activation by stimulating the MEK/ERK pathway, ultimately influencing the development of HGNEC.